Direct kinetic correlation of carriers and ferromagnetism in Co2+: ZnO - Kittilstved, Kevin R; Schwartz, Dana A; Tuan, Allan C; Heald, Steve M; Chambers, Scott A; Gamelin, Daniel R (Physical review letters, 2006)
The hypothesis that high-Curie-temperature ferromagnetism in cobalt-doped ZnO (Co2+: ZnO) is mediated by charge carriers was tested by controlled introduction and removal of the shallow donor interstitial zinc. Using oriented epitaxial Co2+: ZnO films grown by chemical vapor deposition, kinetics measurements demonstrate a direct correlation between the oxidative quenching of ferromagnetism and the diffusion and oxidation of interstitial zinc. These results demonstrate controlled systematic variation of a key parameter involved in the ferromagnetism of Co2+: ZnO and, in the process, unambiguously reveal this ferromagnetism to be dependent upon charge carriers. The distinction between defect-bound and free carriers in Co2+: ZnO is discussed.